2016
DOI: 10.1112/s0010437x16007399
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing at infinity on homogeneous spaces of reductive type

Abstract: Abstract. By the collective name of lattice counting we refer to a setup introduced in [10] that aims to establish a relationship between arithmetic and randomness in the context of affine symmetric spaces. In this paper we extend the geometric setup from symmetric to real spherical spaces and continue to develop the approach with harmonic analysis which was initiated in [10].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Theorem 4.3. [18]. Let G be a real reductive group and H < G a connected subgroup of G with real algebraic Lie algebra.…”
Section: Volume Weights On G/hmentioning
confidence: 99%
“…Theorem 4.3. [18]. Let G be a real reductive group and H < G a connected subgroup of G with real algebraic Lie algebra.…”
Section: Volume Weights On G/hmentioning
confidence: 99%
“…2.1. Further let H < G be a subgroup which is reductive in G (as in [12]). With these data we form the homogeneous space of reductive type Z := G/H .…”
Section: Homogeneous Spaces Of Spherical Typementioning
confidence: 99%
“…Finally, we mention that in [12] we have studied a more qualitative property of decay of smooth L p -functions which are not necessarily matrix coefficients of a Harish-Chandra module. More precisely, we showed that on a reductive homogeneous space the smooth vectors in the Banach representation L p (Z ) all belong to the space of continuous functions vanishing at infinity.…”
mentioning
confidence: 99%